Concerted Multisectoral Strategic Interventions towards Sustaining SMEs During and Post Covid –19 Disruptions - Isoe, Headmound Okari (Journal of Strategic Management, 2022)
The crisis occasioned by the Covid-19 pandemic and the resulting containment measures caused major negative effects on the global economy. For instance, it cut by 3 to 8 percentage points the GDP growth of African economies. This crisis triggered a myriad of interventions from various players to mitigate or avoid the collapse of SMEs. This paper sought to analyse and document some of the strategic interventions adopted and those available for consideration in the quest to sustain SMEs during and post Covid-19 crisis. The paper was anchored on the premise that SMEs can only survive and be sustained by the different players in the business ecosystem taking deliberate measures towards mitigating the absurdities of the crisis. The paper considered more than 100 journal articles and reports by various governments and international agencies. After analysing the various strategies, the paper concluded that each key player, including governments, financial institutions, SMEs and the wider business community, has initiated and implemented strategies to ensure the sustenance of SMEs during and post Covid-19 crisis. Some of the identified strategies by some of the governments include; mobilisation of financial resources, direct funding and support programs, Fiscal stimulus programs, monetary incentives for SMEs, exemption or reductions and some instances deferred tax obligations. Financial institutions on the other hand have introduced rescheduling of repayment plans of existing loans to ensure that SMEs have sustainable liquidity and not overstretched to meet their debt obligations in the short-term. The wider business community have made efforts to strengthen existing symbiotic partnerships to protect and ensure survival of the business ecosystem. Finally, the SMEs are encouraged to embrace technology and innovation, review and realign their distribution channels, ensure new product developments aligned to containment measures, Seek partnerships and Development of new market access approaches. From the reviewed literature, the paper established that most of these strategies have proven to be of profound value. The paper recommends that the different players intensify the deployment of the discussed strategies to ensure that SMEs remain afloat during and post Covid. The paper further recommends that policy makers create an enabling policy framework to enhance the adoption and operationalisation of the discussed strategies to ensure the survival and sustenance of the SMEs during and post the Covid-19 disruptive times. Keywords: Multisectoral, Strategic Interventions, Post Covid-19